A review of heat treatment on polyacrylonitrile fiber - Rahaman, M. S. A.; Ismail, Ahmad Fauzi; Mustafa, A. (Elsevier Ltd., 2007)
Developing carbon fiber from polyacrylonitrile (PAN) based fiber is generally subjected to three processes namely stabilization, carbonization, and graphitization under controlled conditions. The PAN fiber is first stretched and simultaneously oxidized in a temperature range of 200e300 C. This treatment converts thermoplastic PAN to a non-plastic cyclic or a ladder compound. After oxidation, the fibers are carbonized at about 1000 C in inert atmosphere which is usually nitrogen. Then, in order to improve the ordering and orientation of the crystallites in the direction of the fiber axis, the fiber must be heated at about 1500-3000 C until the polymer contains 92e100%. High temperature process generally leads to higher modulus fibers which expel impurities in the chain as volatile by-products. During heating treatment, the fiber shrinks in diameter, builds the structure into a large structure and upgrades the strength by removing the initial nitrogen content of PAN precursor and the timing of nitrogen. With better-controlled condition, the strength of the fiber can achieve up to 400 GPa after this pyrolysis process